THE RESULTS OF EXPERIMENTAL COMPUTER MODELING IN STABILIZATION OF TRANSPEDICULAR SYSTEMS USED IN THE SURGICAL TREATMENT OF VARIOUS PATHOLOGIES OF THE SPINE - Jalilov, T.Ya. (World of Medicine and Biology, 2021)
The proposed method was experimentally modeled using the Solid Works computer program and put into practice in 32 patients aged 13–65 years in the period 2014–2018, with various pathologies of the spine. Of these, 22 (68.75 %) are female, 10 (31.25 %) are male. The patients were operated with transpedicular systems of various configurations. To prevent spontaneous displacement of the screws in the long-term postoperative period, a technique was proposed for creating an additional support point by conducting a transverse connector through a transverse hole made in the spinous process of the vertebra. 2 situations were considered. In the first case, a fixed vertebra with a classically drawn transverse connector and the applied driving forces of pulling the screws out of the vertebral body in eight different directions. The second case was similar to the first one with a difference in conducting the connector through the spinous process of the vertebra. In both groups, the displacement distance increases with an increase in the angle of the vector of the applied force. The force for the screws to exit the channel was 26.561 N/mm2 (MPa). In the second case, it was 31.095 N/mm2 (MPa). The difference was 5 N/mm2. The method of creating an additional support point for transpedicular systems by passing a transverse connector through the spinous process of the vertebra, a statically proven method, increases the stability of transpedicular systems.